A Virtual Platform to Determine the Tensile Properties of Engineered Cementitious Composite - Benny Suryanto; Joshua Kiyoshi Suryanto (Institute of Research and Community Outreach - Petra Christian University, 2020)
The four-point flexural test is now making headway as an alternative laboratory investigative technique for determining the tensile properties of Engineered Cementitious Composite (ECC) to the more traditional, direct/uniaxial tensile test. As the fundamental mechanics of ECC specimens tested in four-point flexure are well understood, it is possible to develop a simple relationship between flexural test results and the tensile properties of this cement composite. This paper extends this development and aims to provide accessible and quick calculation of the tensile properties of ECC via a virtual test environment. To this end, attention is directed towards the test configurations developed earlier at Heriot-Watt University, the University of Michigan, and Sepuluh Nopember Institute of Technology. In this paper, the technical background employed in creating the virtual environment and the computer implementation using the JavaScript programming language are presented. The prototype virtual environment is freely available via the Internet at https://ecc-calculator.netlify.app/.